UKRAINIAN ART IN THE CONTEXT OF THE GEOPOLITICAL CHALLENGE OF 2014-2025 - Babii, Nadiia; Semchuk, Lesia; Chuyko, Oleg; Maryschuk, Tetiana; Beilakh, Oksana (Veredas do Direito, 2026)
The publication explores traditional and contemporary art and discourses, contextually generated socio-artistic practices that are currently being produced in Ukraine in the realities of war. The socio-cultural reflection on the modes of existence of war as a phenomenon of physical reality and as a discursive construct that exist simultaneously and are reproduced through material and symbolic (textual) parameters is taken into account. It is noted that reactive and reflexive artistic practices reflect the understanding of the novelty of “war in the city”, which requires the use of urban strategies of resistance. Existential differences in the creation of narratives for different target audiences of both local and global society are determined. The research methodology is based on own objective observation and analytics, which allowed identifying a number of typical artistic practices that were instantly transformed into artistic mobilization strategies of resistance. The conclusions indicate that artistic artivism has once again actualized the issue of the social content of art, the meaning of culture, national language and symbols, mobilizing artists to the processes of modeling current reality and its retranslating. Additionally, the role of museums and other institutions as places of refuge, humanitarian and cultural centers for preserving identity is revealed.